Differences in inflammatory marker profiles and cognitive functioning between deficit and nondeficit schizophrenia - Wang, Dandan; Wang, Yewei; Chen, Yan; Yu, Lingfang; Wu, Zenan; Liu, Ruimei; Ren, Juanjuan; Fang, Xinyu; Zhang, Chen (Frontiers in Immunology, 2022)
Deficit schizophrenia (DS) patients are regarded as a homogenous subtype of schizophrenia presenting primary and enduring negative symptoms. This study aimed to compare the differences in cognitive functioning and plasma levels of C-reactive protein (CRP) and inflammatory cytokines among DS patients, non-DS (NDS) patients and healthy controls (HCs). A total of 141 schizophrenia patients and 67 HCs were included in this study. The schizophrenia patients were divided into DS (N= 51) and NDS (N=90) groups according to the Proxy for the Deficit Syndrome Scale (PDS). The Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) were used to evaluate the clinical symptoms and cognitive performances, respectively. The plasma level of CRP, IL-1β, Il-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-17, TNF-α, and IFN-γ were measured using enzyme-linked immunosorbent assays (ELISAs). Our results showed that DS patients had the worst cognitive performance, especially in the immediate memory, attention and language dimensions, compared to the NDS and HC groups. Compared to the HCs group, DS patients had higher levels of CRP, IL-1β, IL-6, IL-8, IFN-γ and total proinflammatory cytokines, and NDS patients had higher levels of IL-1β, IFN-γ and proinflammatory cytokines. We also found that CRP levels were significantly increased in DS patients compared to NDS patients. Moreover, stepwise logistic regression analysis revealed that CRP is an independent risk factor for DS. The significant differences in cognitive performance and inflammatory components among groups provide evidence that deficit syndrome is an independent endophenotype of schizophrenia patients with unique immune-inflammatory characteristics.